FACTORS INFLUENCING THE PROCESS OF PERINEAL WOUND HEALING IN POSTPARTUM WOMEN IN SERUI HOSPITAL, PAPUA - Yuli Triyani; Ivon Diah Wittiarika; Gatut Hardianto (UNIVERSITAS AIRLANGGA, 2021)
Background: The process of giving birth has a risk of perineal rupture. The 4.9% incidence of delayed perineal wound healing resulted from non-fused perineal wounds and clinical infection. This process can be interrupted or recovery delayed due to various factors such as age, nutrition, pain, and poor hygiene. This study aims to analyze the factors that influence the healing process of perineal wounds in postpartum mothers. Method: analytic observational research method with cross sectional approach and analityc statistic Chi-Square. The samples are postpartum woman in Serui Hospital, Papua. The number of samples were 30 respondents with purposive sampling technique. The instrument used was the REEDA scale, the pain scale, the food consumption survey with the 24-hour recall method and the personal hygiene questionnaire. Results: The results of statistical tests showed a relationship between pain with the perineal wound healing process is p 0,017, age with the perineal wound healing process is p 0,000, nutrition with the perineal wound healing process is p 0,000, and personal hygiene pain with the perineal wound